Repetition Suppression Dissociates Spatial Frames of Reference in Human Saccade Generation - Van Pelt, Stan; Toni, Ivan; Diedrichsen, Jörn; Medendorp, W. Pieter (Journal of neurophysiology, 2010)
The path from perception to action involves the transfer of information across various reference frames. Here we applied a functional magnetic resonance imaging (fMRI) repetition suppression paradigm to determine the reference frame(s) in which the cortical activity is coded at several phases of the sensorimotor transformation for a saccade, including sensory processing, saccade planning, and saccade execution. We distinguished between retinal (eye-centered) and nonretinal (e.g., head-centered) coding frames in three key regions: the intraparietal sulcus (IPS), frontal eye field (FEF), and supplementary eye field (SEF). Subjects ( n = 18) made delayed saccades to one of five possible peripheral targets, separated at intervals of 9° visual angle. Target locations were chosen pseudorandomly, based on a 2 × 2 factorial design, with factors retinal and nonretinal coordinates and levels novel and repeated. In all three regions, analysis of the blood oxygenation level dependent dynamics revealed an attenuation of the fMRI signal in trials repeating the location of the target in retinal coordinates. The amount of retinal suppression varied across the three phases of the trial, with the strongest suppression during saccade planning. The paradigm revealed only weak traces of nonretinal coding in these regions. Further analyses showed an orderly representation of the retinal target location, as expressed by a contralateral bias of activation, in the IPS and FEF, but not in the SEF. These results provide evidence that the sensorimotor processing in these centers reflects saccade generation in eye-centered coordinates, irrespective of their topographic organization.